Workforce Gender Disparities: A Cross-National Analysis of Switzerland, the United States, and Singapore - Chun Grace, Yip Pei (Digital Repository of Theses, 2026)
Gender gaps in workforce participation, leadership, and pay persist even in high-income economies; however, their underlying drivers and effective policy responses vary significantly across national contexts. This study comparatively examines Switzerland, the United States, and Singapore to investigate how cultural expectations and institutional capacity jointly shape gender parity outcomes and their broader socioeconomic implications. Grounded in Social Role Theory and Institutional Theory, the study addresses two key research questions: (1) which cultural and institutional factors influence the transfer and effectiveness of gender parity policies across Western and Asian contexts; and (2) how gender-related labour market conditions are associated with income inequality. An explanatory sequential mixed-method design based on secondary data is employed. The qualitative phase involves document analysis of approximately 50–60 sources—including policy documents, institutional reports, academic literature, and media discourse—across multiple sectors, using thematic coding to identify recurring patterns in governance, organisational practices, and social norms. The quantitative phase applies cross-national panel regression analysis using country-year observations from 40 countries over a 20-year period (2005–2024) to examine the relationship between the Gini coefficient and key gender-related indicators, including female labour force participation, women’s empowerment, gender wage discrepancy, and women’s leadership representation. Qualitative findings are subsequently used to interpret and contextualise statistical results. The findings highlight the critical importance of alignment between institutional “hardware” and cultural “software.” While coherent legal frameworks, effective enforcement mechanisms, and supportive policies—such as childcare provision and parental leave—facilitate progress, their impact is often constrained by persistent gender norms that shape caregiving responsibilities and leadership expectations. Quantitative results further support this interpretation, indicating that higher levels of women’s empowerment, labour force participation, and leadership representation are associated with lower income inequality, whereas larger gender wage gaps correspond to higher inequality. The study concludes that achieving sustainable gender parity requires more than policy adoption alone. Effective interventions must integrate institutional enforcement, supportive social infrastructure, and organisational practices that mitigate role-congruity bias and strengthen leadership pipelines. By providing a comparative and theoretically grounded analysis, this research offers context-sensitive yet policy-relevant insights for advancing gender equality across diverse institutional environments. Keywords: Gender Disparity; Income Inequality; Institutional Theory; Social Role Theory; Switzerland; United States; Singapore